The Influence of Leadership and Work Environment toward Organziational Citizenship Behavior (OCB) through Work Satisfaction - Dedi Purwana; Argo Ahmad; Ari Saptono (International Journal on Advanced Science, Education, and Religion, 2020)
This article aimed to analyse the influence of leadership on job satisfaction of employees at the Research Agency and Human Resource of Maritime and Fisheries, the influence of the work environment on job satisfaction of employees, the influence of leadership on Organizational Citizenship Behavior (OCB) of employees, the influence of the Work environment on OCB of employees, the effect of job satisfaction of employees, the influence of leadership on OCB of employees, and the influence of the work environment on OCB of employees through Job Satisfaction as an intervening variable. This research was quantitative by using the survey method that has character to explain the causal relationship or ordinary correlational, namley path analysis (pathanalysis). The respondents were 218 employees in the Research Agency and Human Resource of Maritime and Fisheries. The results of the study show that: 1) There were the effect of leadership on job satisfaction among employees of Research Agency and Human Resource of Maritime and Fisheries. 2) There was the influence of the work environment on job satisfaction of employees 3) There were influence of leadership on OCB 4) there was the influence of the work environment on OCB 5) the influence of job satisfaction on OCB 6) the influence of leadership on Organizational Citizenship Behavior (OCB) on Research Agency and Human Resource of Maritime and Fisheries through Job Satisfaction as an Intervening variable, and 7) the existence the influence of the work environment on Organizational Citizenship Behavior (OCB) through Job Satisfaction as an intervening variable. Keywords: Organizational Citizenship Behavior, Leadership, Job Satisfaction